On the use of menus in sequential common agency - Giacomo Calzolariy; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2008)
We illustrate, by means of two examples, why assuming the principals offer simple menus (i.e. collections of payoff-relevant alternatives) as opposed to more general mechanisms may preclude a complete characterization of the set of equilibrium outcomes in certain sequential contracting environments. We then discuss how refinements of the solution concept, or enrichments of the menus that allow for recommendations, may restore the possibility of using menus to obtain a complete equilibrium characterization.
Keywords: D89; C72; 330; sequential contracting; mechanism design; menus theorems